Legislative Governance in the Field of Training and Career Development - Abdul Hameed , Ahmed (Journal of Legal Sciences, 2025)
Legislative governance is one of the important and emerging topics that deals with modern mechanisms and methods to raise legislative work to the level of legislative quality. As is known, the legislation that regulates the affairs of public employees in the public service, specifically in the field of training and administrative development, still suffers from deficiencies in organization in terms of legislative formulation on the part of, On the other hand, these legislations have adopted and still adopt classical school methods in training, in addition to the absence of technological support and financial accreditation. This is because the process of training and development, and then job evaluation to know the feedback or results of training, is an ongoing process and does not stop at a certain point. It is developed in terms of training methods and the level of training, according to the job ladder, to ensure the advancement of competent and qualified employees to occupy higher positions, This continuous and sustainable process must be surrounded by administrative and legal guarantees for the employee, allowing him to confront management in the event of its abuse of authority. This study focuses on the most important obstacles to training, development, and job performance evaluation, and the role of legislative governance in controlling the rules governing them.